Bangladesh, South Asia, and the world - Ahmed, Emajuddin; Abul Kalam (Professor of International Relations); International Studies Association, Bangladesh (Dhaka, Bangladesh : Academic Publishers in association with International Studies Association, Bangladesh, 1992)
Chiefly on South Asian affairs; most papers presented at a seminar organized by the International Studies Association, Bangladesh, in Dhaka on 10 August 1990.
Includes bibliographical references.
Keywords: Bangladesh -- Politics and government -- 1971-; South Asia -- Politics and government; Bangladesh -- Relations -- South Asia; South Asia -- Relations -- Bangladesh